A highly sensitive LC–MS/MS method for simultaneous determination of glycyrrhizin and its active metabolite glycyrrhetinic acid: Application to a human pharmacokinetic study after oral administration. (18th July 2017) - Suzuki, Tsuneharu; Tsukahara, Michiko; Akasaka, Yuko; Inoue, Hideo
Abstract: A highly sensitive liquid chromatography tandem mass spectrometry (LC–MS/MS) method for simultaneous determination of glycyrrhizin (GL) and its active metabolite, glycyrrhetinic acid (GA), from human plasma was validated and applied to a human pharmacokinetic study. The analytes were extracted from human plasma using an Oasis MAX cartridge and chromatographic separation was performed on an Inertsil ODS‐3 column. The detection was performed using an API 4000 mass spectrometer operating in the positive electrospray ionization mode. Selected ion monitoring transitions of m / z 823 → 453 for GL and m / z 471 → 149 for GA were obtained. The response was a linear function of concentration over the ranges of 0.5–200 ng/mL for GL and 2–800 ng/mL for GA (both R 2 > 0.998). Using this method, the pharmacokinetics of GL after single oral administration of a clinical dose (75 mg) to six healthy male Japanese volunteers were evaluated. GL was detected in the plasma of all subjects and the average peak concentration was 24.8 ± 12.0 ng/mL. In contrast, peak concentration of GA was 200.3 ± 60.3 ng/mL, i.e. 8‐fold higher than that of GL. This is the first report clarifying pharmacokinetic profiles of GL and GA simultaneously at a therapeutic oral dose of a GL preparation.